Assessment of disability in idiopathic inflammatory myopathy: a call for linearity. (7th December 2021) - Min, Minoesch; Walter, Anne W; Lim, Johan; Eftimov, Filip; Verhamme, Camiel; de Visser, Marianne; van Schaik, Ivo N; Aggarwal, Rohit; de Haan, Rob J; van der Kooi, Anneke J; Raaphorst, Joost; ,
Abstract: Objectives: To evaluate the clinimetric properties of the Academic Medical Centre Disability Score (ALDS) in patients with idiopathic inflammatory myopathy (IIM). Methods: We used prospectively collected data of IIM patients who completed a phase-2 study with first-line IVIG monotherapy. The ALDS is a patient-reported questionnaire which contains 25 items relevant for disability in myositis. ALDS and all core set measures (CSMs) for myositis [including HAQ-Disability Index (HAQ-DI)] were evaluated at baseline and 9 weeks follow-up. In addition, the 2016 ACR/EULAR myositis response criteria outcome called Total Improvement Score (TIS) was evaluated at 9 weeks. We examined floor/ceiling effects, reliability and construct validity of the ALDS. To examine known-group validity, ALDS change scores over time were compared with TIS and physician impression of clinical response. Results: Nineteen patients with IIM [median age 59 years, 12 (63%) female] were enrolled. At baseline, ALDS showed a median score of 65.4 (IQR 58.2–73.5), good Cronbach's alpha (α = 0.84) and a small ceiling effect (11%). Construct validity was confirmed by moderate to strong correlations between ALDS and HAQ-DI [rs  = −0.57 (baseline); −0.86 (follow-up)]. ALDS change score correlated with TIS (rs  = 0.70), discriminated between responders and non-responders (TIS ≥ 40; P  = 0.001), between groups based on physician impression of clinical response ( P  = 0.03), and detected deterioration. Conclusion: The ALDS showed promising clinimetric properties and detected relevant changes in disability in patients with myositis. These results warrant further investigations.